Case Report: Traumatic obturator hip dislocation with subtrochanteric fracture in an 8-year-old child - Huang, Shuming; Fang, Kanghao; Xing, Hailin; Lan, Shuhua; Wu, Quanzhou (Frontiers in Surgery, 2025)
BackgroundObturator-type hip dislocation is a rare condition in pediatric patients, with the simultaneous occurrence of an ipsilateral subtrochanteric femoral fracture being exceptionally uncommon. Although various treatment methods have been described for hip dislocation or subtrochanteric femoral fractures, managing these injuries remains challenging due to the potential risk of femoral head avascular necrosis and concerns about fixation stability.Case presentationAn 8-year-old boy sustained a traumatic obturator hip dislocation and an ipsilateral subtrochanteric fracture following a fall from a height. Closed manual reduction of the hip dislocation was performed under general anesthesia, followed by internal fixation of the fracture using an adult proximal humerus locking plate. After 3 years of follow-up, the patient showed complete fracture healing and achieved a full, painless range of hip motion without any complications.ConclusionThis case describes a rare instance of traumatic obturator-type hip dislocation with an ipsilateral subtrochanteric femoral fracture in a child. It highlights an effective treatment approach for managing this complex injury.